New knowledge transfer practices - Sancassani S. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
In sectors like the agrifood industry, the complexity of the problems needing to be tackled often requires solutions that integrate expertise from very different disciplinary areas. From this point of view, the proposal made several years ago by economist Richard Normann to allow the development of a “value chain” towards the “value constellation” takes on a new meaning, not only for production processes, but also for the formulation of new strategies for the development of innovation. In order to enable the formation of the constellation in the innovation ecosystem, it becomes necessary to train those able to act as real “brokers” – or intermediaries – in the networks, connecting stakeholders who are not traditionally connected, but who create “new combinations” of technological solutions, essential for generating innovations. Following this, the chapter explores the instruments provided by digital technologies and cyber networks for improving interaction and consolidating an open and collaborative approach between different actors in the innovation systems. The vast range of new instruments/environments provided by the Web can contribute to the creation of an “ecosystem” in which the innovation brokers are supported in all the key processes connected with their work.